THE MOLECULAR INVESTIGATIONS ON PHYLOGENETIC RELATIONSHIPS AND SYSTEMATIC BOUNDARIES OF SPECIES BELONG TO THE SUBGENUS ARTEMISIA LESS OF THE GENUS ARTEMISIA L. (ASTERACEAE) IN TURKEY - TUKUR, UMMU (Fırat Üniveristesi, 2020)
Bu moleküler çalışmada, Artemisia altcinsinin 14 türüne ait 25 farklı populasyondan alınan 30 örnekten 44 birey incelenmiştir. Herbaryum örneklerindeki bireylerin sayısına bağlı olarak, her bir numune için aynı etiket bilgisine sahip 1 ila 3 birey kullanılmıştır. Toplamda ise her tür için farklı veya aynı etiket bilgisine sahip 2 ila 4 birey incelenmiştir. İncelenen tüm bireylere ait kloroplast DNA'nın psbA-trnH bölgesi ve ITS1-5.8 gen - ITS2 nükleer DNA bölgelerinin DNA dizileri belirlenmiştir. Bu moleküler çalışmanın sonuçlarına göre, incelenen türler % 88 boostrap değerine sahip iki gruba ayrılmıştır. Türlerin DNA dizisi benzerliğine dayanan iki moleküler grup ile türlerin reseptakulumunun tüy durumuna göre oluşturulan iki morfolojik grup arasında tam bir uygunluk yoktur. Artemisia altcinsi türlerinin reseptakulumlarının tüylü veya tüysüz olmasına bağlı olarak yeni altcinslere veya bölümlere bölünmesinin moleküler olarak anlamlı olmadığı bulunmuştur. Artemisia altcinsinin incelenen 14 türü arasında gen akışı ve hibridizasyon olmadığı ve bu 14 türün de türleşmesini tamamladıkları bulunmuştur.

In this molecular study, 44 individuals of 30 specimens taken from 25 different populations belong to 14 species of the subgenus Artemisia were examined. Depending on the numbers of individuals in the herbarium specimens, between 1 and 3 individuals with the same label information were used for each specimen. 2 to 4 individuals with the different or same label information were examined for each species in total. DNA sequences which are the psbA-trnH region of chloroplast DNA and ITS1-5.8 gene - ITS2 regions of nuclear DNA belonging to all examined individuals were determined. According to the results of this molecular study, the studied species are divided into two groups with 88% boostrap value. There is no complete agreement between the two molecular groups which are based on the DNA sequence similarity of species and the two morphological groups formed according to the hair condition of the receptacle of species. Dividing of the subgenus Artemisia species into new subgenera or sections depending on whether their receptacles were hairy or hairless was not found to be molecularly significant. It was found that there were no gene flow and hybridization between the 14 studied species of the subgenus Artemisia and these 14 species were also completed their speciation.
Artemisia L. (Asteraceae) cinsinin Artemisia less. alt cinsine ait Türkiye'deki türlerin sistematik sınırları ve filogenetik ilişkileri üzerine moleküler incelemeler
Keywords: Biyoloji